Pengaruh athlete endorsement dan online review terhadap keputusan pembelian brand olahraga Ortuseight yang dimediasi kepercayaan - Sasilintang, Imadulhaq Razan; Bachri, Syamsul; Muzakir; Farid (Universitas Widya Mataram, 2025)
This study aims to examine the influence of athlete endorsement and online reviews on consumer trust and its impact on purchase decisions for Ortuseight products. A quantitative approach was employed using Partial Least Square–Structural Equation Modeling (PLS-SEM) for data analysis. Data were collected from 120 respondents who are consumers of the Ortuseight brand through purposive sampling. The results indicate that both athlete endorsement and online reviews have a positive and significant influence on consumer trust. Furthermore, consumer trust is proven to mediate the relationship between the two independent variables and purchase decisions. These findings highlight that a strategic combination of credible athlete endorsements and informative online reviews can effectively enhance consumer trust and drive purchase decisions for local sports brands.